Controlled-release of apatinib for targeted inhibition of osteosarcoma by supramolecular nanovalve-modified mesoporous silica - Wang, Xinglong; Li, Gongke; Li, Ke; Shi, Yu; Lin, Wenzheng; Pan, Chun; Li, Dandan; Chen, Hao; Du, Jianwei; Wang, Huihui (Frontiers in Bioengineering and Biotechnology, 2023)
Targeted delivery of antitumor drugs has been recognized as a promising therapeutic modality to improve treatment efficacy, reduce the toxic side effects and inhibit tumor recurrence. In this study, based on the high biocompatibility, large specific surface area, and easy surface modification of small-sized hollow mesoporous silica nanoparticles (HMSNs), β-cyclodextrin (β-CD)-benzimidazole (BM) supramolecular nanovalve, together with bone-targeted alendronate sodium (ALN) were constructed on the surface of small-sized HMSNs. The drug loading capacity and efficiency of apatinib (Apa) in HMSNs/BM-Apa-CD-PEG-ALN (HACA) were 65% and 25%, respectively. More importantly, HACA nanoparticles can release the antitumor drug Apa efficiently compared with non-targeted HMSNs nanoparticles in the acidic microenvironment of the tumor. In vitro studies showed that HACA nanoparticles exhibited the most potent cytotoxicity in osteosarcoma cells (143B cells) and significantly reduced cell proliferation, migration and invasion. Therefore, the drug-efficient release of antitumor effect of HACA nanoparticles is a promising way to treat osteosarcoma.